An 'Opportunistic Interpretation' of Bentham's Panopticon writings. (1st January 2014) - Gombert, Karolina
Abstract : In line with Bentham, who states that no one deserves punishment, not even the offender, this article argues for the development goal of criminal justice systems genuinely to achieve 'justice' for the greatest good of society and the offender. To this end, this article offers an 'opportunistic interpretation' of Bentham's Panopticon writings.